Structure of the effector-binding domain of deoxyribonucleoside regulator DeoR from Bacillus subtilis - Škerlová, Jana; Fábry, Milan; Hubálek, Martin; Otwinowski, Zbyszek; Rezáčová, Pavlína (The FEBS journal, 2014)
UNLABELLED: Deoxyribonucleoside regulator (DeoR) from Bacillus subtilis negatively regulates expression of enzymes involved in the catabolism of deoxyribonucleosides and deoxyribose. The DeoR protein is homologous to the sorbitol operon regulator family of metabolic regulators and comprises an N-terminal DNA-binding domain and a C-terminal effector-binding domain. We have determined the crystal structure of the effector-binding domain of DeoR (C-DeoR) in free form and in covalent complex with its effector deoxyribose-5-phosphate (dR5P). This is the first case of a covalently attached effector molecule captured in the structure of a bacterial transcriptional regulator. The dR5P molecule is attached through a Schiff base linkage to residue Lys141. The crucial role of Lys141 in effector binding was confirmed by mutational analysis and mass spectrometry of Schiff base adducts formed in solution. Structural analyses of the free and effector-bound C-DeoR structures provided a structural explanation for the mechanism of DeoR function as a molecular switch. DATABASES: Atomic coordinates and structure factors for crystal structures of free C-DeoR and the covalent Schiff base complex of C-DeoR with dR5P have been deposited in the Protein Data Bank with accession codes 4OQQ and 4OQP, respectively. STRUCTURED DIGITAL ABSTRACT: C-DeoR and C-DeoR bind by x-ray crystallography (View interaction) DeoR and DeoR bind by molecular sieving (1, 2).
Keywords: roztoky; Bacillus subtilis; vodíková vazba; Schiff Bases; Repressor Proteins; Protein Structure, Tertiary; vazebná místa; represorové proteiny; Protein Structure, Quaternary; sekvence aminokyselin; bakteriální proteiny; substituce aminokyselin; mutageneze cílená; vazba proteinů; Bacterial Proteins; terciární struktura proteinů; Amino Acid Substitution; strukturní homologie proteinů; Amino Acid Sequence; krystalografie rentgenová; Mutagenesis, Site-Directed; Protein Multimerization; Solutions; Models, Molecular; Schiffovy báze; Protein Structure, Secondary; molekulární modely; sekundární struktura proteinů; Hydrogen Bonding; kvarterní struktura proteinů; multimerizace proteinu; Crystallography, X-Ray; Protein Binding; Binding Sites; Structural Homology, Protein